Faktor Determinan Pengembangan Kapasitas Perawat dalam Pelayanan Kesehatan - Suprapto Suprapto; Trimaya Cahya Mulat; Ismail Ismail; Erlina Y Kongkoli (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; Health services are public services carried out by organizations or health service facilities as an effort to fulfill the basic needs of the community. Aim; determine the determinant factors in developing the capacity of nurses in health services. Method; This research is qualitative, the data sources used are primary and secondary data sources. Data were collected by observation, interviews, and document studies. The data analysis used was descriptive qualitative through in-depth interpretation and meaning by simplifying data, presenting data, and making conclusions, and validating by data triangulation. Results: That the determinant factors determine the capacity development of nurses as follows; leadership; commitment; resources; culture; spiritual; technology; Conclusion; that it can be stated that the research findings on the strategy of developing the capacity of nurses in health services can be realized by; education and training based on spiritual aspects and technological aspects in developing nurse capacity.